2012
DOI: 10.1007/s00424-012-1167-y
|View full text |Cite
|
Sign up to set email alerts
|

Sodium nitrite therapy rescues ischemia-induced neovascularization and blood flow recovery in hypertension

Abstract: Background Arterial hypertension is a major risk factor that can lead to complication of peripheral vascular disease due, in part, to endothelial dysfunction. Because sodium nitrite (SN) can be converted to nitric oxide (NO), which counteracts endothelial dysfunction, we explored the effect of nitrite on neovascularization following hind-limb ischemia in different models of hypertension (HT). Methods and results Chronic delivery of angiotensin-II (Ang-II, 400ng/Kg/min) or N(omega)-nitro-L-arginine-methyl-est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Inhibition of XOR prevented this recovery, suggesting a role for XOR-mediated reduction of nitrite to NO in blood flow under these conditions, as suggested in in vitro studies (Li et al, 2003;Amin et al, 2012). Hypertensive mice also demonstrated a decrease in cGMP levels compared to control mice in the hind limb (Amin et al, 2012). However, treatment with sodium nitrite was found to significantly enhance cGMP levels; thus in this study, it was suggested that sodium nitrite could be used as a therapy for full recovery of blood flow.…”
Section: Effect Of Dietary Nitratessupporting
confidence: 53%
See 1 more Smart Citation
“…Inhibition of XOR prevented this recovery, suggesting a role for XOR-mediated reduction of nitrite to NO in blood flow under these conditions, as suggested in in vitro studies (Li et al, 2003;Amin et al, 2012). Hypertensive mice also demonstrated a decrease in cGMP levels compared to control mice in the hind limb (Amin et al, 2012). However, treatment with sodium nitrite was found to significantly enhance cGMP levels; thus in this study, it was suggested that sodium nitrite could be used as a therapy for full recovery of blood flow.…”
Section: Effect Of Dietary Nitratessupporting
confidence: 53%
“…In a mouse model of ischemic (hypoxic) hind-limb, hypertensive mice showed a significantly decreased blood flow compared to sham operated mice, and blood flow could be recovered in both hypertensive and normotensive mice when treated with sodium nitrite compared to non-treated mice. Inhibition of XOR prevented this recovery, suggesting a role for XOR-mediated reduction of nitrite to NO in blood flow under these conditions, as suggested in in vitro studies (Li et al, 2003;Amin et al, 2012). Hypertensive mice also demonstrated a decrease in cGMP levels compared to control mice in the hind limb (Amin et al, 2012).…”
Section: Effect Of Dietary Nitratesmentioning
confidence: 60%
“…Accordingly, the present study shows that lead‐induced hypertension was found in rats, which presented whole‐blood lead levels of 11.5 ± 1.2 µg/dL. Therefore, to expand the understanding of lead‐induced hypertension, we assessed plasma metabolites of NO (NOx levels), which reflect the bioavailability of NO . In support of previous studies, our present findings show that rats intoxicated with a similar dosage of lead acetate presented reductions in the NO bioavailability associated with increases in systolic blood pressure .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, the therapeutic potential effect of nitrite in the treatment of a number of cardiovascular including ischemia/reperfusion (I/R) injured; hypercholesterolemia induced microvascular inflammation as well as ischemia-induced angiogenesis are established. [4] Previous reports indicate that these compounds may damage the nervous system, liver, kidneys, and spleen of small fish. [5] In addition, some study suggests that infant formula has too much nitrite would have the possibility of methaemoglobinaemia.…”
Section: Introductionmentioning
confidence: 99%